Factors affecting the use of e-commerce in creative industries: Empirical evidences from SMES in Jabodetabek-Indonesia - Donny Oktavian Syah; Rambat Lupiyoadi; Adi Pramudita Tjiptadi (Jurnal Siasat Bisnis)
The goal of this research is to identify factors that influences: organizational readiness, the external pressure, the ease of using, and final factor benefit that can be obtained from the use of e-commerce in SMEs Creative Industries in Jabodetabek.